2011
DOI: 10.1111/j.1759-8893.2011.00056.x
|View full text |Cite
|
Sign up to set email alerts
|

The patterns of outpatient off-label carbamazepine use and the potential impact of regulatory labelling process in Taiwan

Abstract: Background Carbamazepine has been associated with severe cutaneous adverse drug reactions (ADR). It is important for patients with these ADRs under off-label prescriptions are not eligible for drug injury relief in Taiwan. We conducted a study to depict the demography and possible factors related to the off-label carbamazepine use in Taiwan. We also explored the policy influence of carbamazepine use. Methods We used the dataset of one million randomly-sampled insured persons in the Taiwan National Health Insur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Although new users of carbamazepine decreased dramatically over time, concerns have been raised due to very extensive off‐label use of carbamazepine found in our study, which has also been pointed out in a previous study in Taiwan . There may be several explanations for this phenomenon.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Although new users of carbamazepine decreased dramatically over time, concerns have been raised due to very extensive off‐label use of carbamazepine found in our study, which has also been pointed out in a previous study in Taiwan . There may be several explanations for this phenomenon.…”
Section: Discussionsupporting
confidence: 70%
“…There may be several explanations for this phenomenon. First, the regulator‐approved indications for carbamazepine in Taiwan are epilepsy, trigeminal neuralgia, bipolar disorder, and diabetes insipidus, but there are many other indications supported by literature, such as peripheral neuropathy and schizophrenia . Second, the proportion of off‐label use was much lower when we analyzed not only the first prescriptions (eg, 91% in 2005 and 80% in 2014) but all the prescriptions of carbamazepine (eg, 56% in 2005 and 38% in 2014), which indicated that physicians may be unable to make definitive diagnosis upon the first carbamazepine prescriptions.…”
Section: Discussionmentioning
confidence: 95%